Mast-cell infiltration of airway smooth muscle in asthma. - Brightling, C; Bradding, P; Symon, F; Holgate, S; Wardlaw, A; Pavord, I (2002)
BACKGROUND: Asthma and eosinophilic bronchitis are characterized by similar inflammatory infiltrates in the submucosa of the lower airway. However, eosinophilic bronchitis differs from asthma in that there is no variable airflow obstruction or airway hyperresponsiveness in the former condition. We tested the hypothesis that there were differences between the two conditions in the microlocalization of mast cells within the airway smooth muscle. METHODS: Immunohistochemical analysis of bronchial-biopsy specimens was completed in 17 subjects with asthma, 13 subjects with eosinophilic bronchitis, and 11 normal controls recruited from two centers. RESULTS: Both groups with disease had a similar degree of submucosal eosinophilia and thickening of the basement membrane and lamina reticularis. By contrast, the number of tryptase-positive mast cells in the bundles of airway smooth muscle from subjects with asthma (median, 5.1 mast cells per square millimeter of smooth muscle [range, 0 to 33.3]) was substantially higher than that in subjects with eosinophilic bronchitis (median, 0 mast cells per square millimeter; range, 0 to 4.8) and that in normal controls (median, 0 mast cells per square millimeter [range, 0 to 6.4]; P<0.001 for the comparison among the three groups). T cells and eosinophils were not usually seen in the airway smooth muscle in any of the groups. CONCLUSIONS: The infiltration of airway smooth muscle by mast cells is associated with the disordered airway function found in asthma.